Quantitative Comparison of Three Rat Models of Achilles Tendon Injury: A Multidisciplinary Approach - Huegel, Julianne (J Biomech, 2019)
The Achilles tendon, while the strongest and largest tendon in the body, is frequently injured. Inconclusive evidence exists regarding treatment strategies for both complete tears and partial tears. Well-characterized animal models of tendon injury are important for understanding physiological processes of tendon repair and testing potential therapeutics. Utilizing three distinct models of rat Achilles tendon injury, the objective of this study was to define and compare the effects and relative impact on tendon properties and ankle function of both tear severity (complete tear versus partial tear, both with postoperative immobilization) and immobilization after partial tear (partial tear with versus without immobilization). We hypothesized that a complete tear would cause inferior post-injury properties compared to a partial tear, and that immediate loading after partial tear would improve post-injury properties compared to immobilization. All models were reproducible and had distinct effects on measured parameters. Injury severity drastically influenced tendon healing, with complete tear causing decreased ankle mobility and tendon mechanics compared to partial tears. One week of plantarflexion immobilization had a strong effect on animals receiving a partial tear. Tendons with partial tears and immobilization failed early during fatigue cycling three weeks post-injury. Partial tear without immobilization had no effect on ankle range of motion through dorsiflexion at any time point compared to the pre-surgery value, while partial tear with immobilization demonstrated diminished function at all post-injury time points. All three models of Achilles injury could be useful for tendon healing investigations, chosen based on the prospective applications of a potential therapeutic.